HOME VISIT SEBAGAI STRATEGI PEMBELAJARAN AGAMA ISLAM PADA MASA PANDEMI COVID-19 - Moh. Anik Mustofa; Rahmat Aziz; Ahmad Fatah Yasin (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
The Covid-19 pandemic has changed the face-to-face learning system to online. Online learning causes many obstacles, so teachers make home visits as an PAI learning strategy during the Covid-19 pandemic. This study aims to analyze the learning strategy of Islam in SMA Negeri 1 Glenmore, Banyuwangi Regency. This research adopts a qualitative approach with a case study method. Data were collected through observation, interviews and documentation. The data collected was then analyzed using the theory of Miles and Huberman, namely reducing, presenting and drawing conclusions. While the data validation technique is triangulation of data and data sources. This research shows that: a) the teacher prepares a lesson plan that is adapted to the students' condition in implementing the strategy home visit; b) worship activities, discipline, student character are important aspects that the teacher pays attention to when conducting lessons home visit; c) the evaluation process is home visit carried out in a simple way to measure learning achievement using the strategy home visit. This research must be followed up by testing the effectiveness of home visits in PAI learning during the Covid-19 pandemic.